Peningkatan Kadar Protein Pada Kulit Umbi Singkong (Manihot esculenta Crantz Sin M. Utilissima Pohl) Melalui Proses Fermentasi - Parlindungan, John Yoro; Andari, Gardis (AGRICOLA, 2021)
Research has been conducted on increasing protein levels in cassava skin through the fermentation process. Cassava skin is an organic waste that if not handled well feared can cause environmental pollution. The purpose of the research to reduce waste, also make use of cassava skin to have a value. The phase of the research is the waste of cassava skin cleaned from the skin of Ari then washed and diced with a length of Â± 1 cm. After that analyzed pH, moisture content, and protein content using micro method Kjehdhal. From the results of the analysis, obtained fermentation data is done with pH 6 and water content of 81.6%. Protein levels of fermentation from day 2 to 7th day. Obtained using microanalysis Kjehdhal participated 1.52%; 2.27%; 6.93%; 7.62%; 3.79%; 0.57%. From this research can be concluded that the fermentation of cassava skin can increase protein levels and can be used as feed additives.